2017
DOI: 10.1016/j.neuroimage.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individualized clinical measures by a generalized prediction framework and multimodal fusion of MRI data

Abstract: Neuroimaging techniques have greatly enhanced the understanding of neurodiversity (human brain variation across individuals) in both health and disease. The ultimate goal of using brain imaging biomarkers is to perform individualized predictions. Here we proposed a generalized framework that can predict explicit values of the targeted measures by taking advantage of joint information from multiple modalities. This framework also enables whole brain voxel-wise searching by combining multivariate techniques such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 110 publications
(119 reference statements)
1
76
0
Order By: Relevance
“…In addition, to utilize as much information as possible, the features were derived from all subjects. Although the classification models were tested with 10-fold cross validation, more solid conclusions can be drawn by examining the performance of biomarkers on new subjects which were excluded from the feature extraction process (Du et al 2015; Meng et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, to utilize as much information as possible, the features were derived from all subjects. Although the classification models were tested with 10-fold cross validation, more solid conclusions can be drawn by examining the performance of biomarkers on new subjects which were excluded from the feature extraction process (Du et al 2015; Meng et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that instead of using a single imaging modality to study its relationship with physiological or cognitive features, people are paying more attention to multimodal fusion, an approach that is able to capitalize on the strength of multiple imaging techniques, since it can uncover the hidden relationships that might be missed from separate unimodal imaging studies [14]. Compelling evidence has confirmed that neuropsychiatric disorders reflect fundamental differences in brain structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…We should note that perfect classification is not the goal of this work, especially since the patients with schizophrenia were receiving antipsychotic and/or mood stabilizing medication during the scanning sessions, thus making it difficult to attribute observed differences to the disease or to the medication [31]–[33]. Instead, our goal is to enable unambiguous quantification of the additive value of each dataset, determination of the combination of datasets that achieves the greatest performance, and quantification of the interaction among datasets within an analysis.…”
Section: Introductionmentioning
confidence: 99%